Trichomo niasis vaginal en gestantes atendidas en los Centros Asistenciales de Tarapoto, periodo de Enero - Agosto 1993 - Najar Ríos, Estefita (1994)
The present study was conducted in health centers Tarapoto, April 9 and Hospital de La Shilcayo, beginning on January 2 this year. We mention that pregnant women in the study were randomly taken when attending their pre natal control; a study with 200 patients was conducted to take samples of vaginal secretion for the identification of Trichomoniasis vaginalisis. All pregnant evaluated a total of 122 a gynecological leucorrhea corresponding to 61%, of which 25 positive cases was obtained was found to Trichomoniasis vaginalisi (20.5%). It may be noted that the study population greater percentage of this infection in pregnant women who have a lower level of education (illiterate) corresponding to 40 per cent was found. We can also observe that the most common sign of Trichomoniasis is leucorrhoea and was obtained with a percentage of 61 percent, remained for longer than 4 months. The causes and cohabitants are those that had a higher percentage of Trichomoniasis and started early sex.